2019
DOI: 10.1016/j.jid.2019.05.022
|View full text |Cite
|
Sign up to set email alerts
|

CCL2-Mediated Reversal of Impaired Skin Wound Healing in Diabetic Mice by Normalization of Neovascularization and Collagen Accumulation

Abstract: Patients with diabetes frequently present with complications such as impaired skin wound healing. Skin wound sites display a markedly enhanced expression of CCL2, a potent macrophage chemoattractant, together with macrophage infiltration during the early inflammatory phase in skin wound healing of healthy individuals, but the association of CCL2 with delayed skin wound healing in patients with diabetes remains elusive. In this study, we showed that, compared with control mice, mice with streptozotocin-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 51 publications
0
58
0
Order By: Relevance
“…CCL2, a chemokine identified in MSC extracellular vesicles, 51 recruits monocytes, memory T cells, and dendritic cells 52,53 . A recent study has shown that CCL2 concentration is decreased in diabetic wounds and topical application of CCL2 improved the delayed healing in diabetic mice 54 . Here, we observed a similar effect, in that when the diabetic wounds healed with the MSC/T/H/S device treatment, the CCL2 expression level in the wound tissue was also significantly elevated compared to the control treatment (Figure 3A).…”
Section: Resultsmentioning
confidence: 99%
“…CCL2, a chemokine identified in MSC extracellular vesicles, 51 recruits monocytes, memory T cells, and dendritic cells 52,53 . A recent study has shown that CCL2 concentration is decreased in diabetic wounds and topical application of CCL2 improved the delayed healing in diabetic mice 54 . Here, we observed a similar effect, in that when the diabetic wounds healed with the MSC/T/H/S device treatment, the CCL2 expression level in the wound tissue was also significantly elevated compared to the control treatment (Figure 3A).…”
Section: Resultsmentioning
confidence: 99%
“…[88][89][90] Despite MCP-1 being generally described as a pro-inflammatory marker, several studies have also reported it to have a robust role in wound healing. [91][92][93] In contrast, RANTES, unlike MCP-1, is generally considered deleterious to the alternative noninflammatory roles of macrophages. 94,95 Therefore, its suppression appears to be desirable toward altering inflammatory polarization states.…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages are key in wound repair and can be central in the process by promoting a resolution of inflammation leading to tissue repair. CCL2, the major macrophage chemoattractant, can reverse the impaired wound healing in diabetic mice (101) and HBD3 can chemoattract macrophages through CCR2 and also modulate pattern recognition receptors relevant to wound repair (102,103). As with all resolution milieu, successful wound healing will be multifactorial, but these data suggest that β-defensins are likely to contribute.…”
Section: Wound Healing Resolutionmentioning
confidence: 99%